PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA KARYAWAN PADA DIVISI PROJECT PT MORA TELEMATIKA INDONESIA TBK CABANG JAKARTA SELATAN - Rahmatullah, Agung; Cay, Sam (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of leadership and non-physical work environment on employee performance in the project division of PT Mora Telematika Indonesia Tbk, South Jakarta Branch. The method used is quantitative. The sampling technique used is saturated sampling with a population and sample of 57 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis testing. The results of this study indicate that leadership has a significant effect on employee performance with a determination coefficient value of 49.3% and hypothesis testing obtained t-value > t-table or (7.317 > 2.004). The non-physical work environment has a significant effect on employee performance with a determination coefficient value of 73.7% and hypothesis testing obtained t-value > t-table or (12.429 > 2.004). Leadership and non-physical work environment simultaneously have a significant effect on employee performance with the regression equation Y = 6.793 + 0.206X1 + 0.725X2. The determination coefficient value is 76.9%, while the remaining 23.1% is influenced by other factors. Hypothesis testing obtained F-value > F-table or (89.948 > 2.78).